2006
DOI: 10.1007/s00220-006-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Power-Law Inflation in Spacetimes Without Symmetry

Abstract: We consider models of accelerated cosmological expansion described by the Einstein equations coupled to a nonlinear scalar field with a suitable exponential potential. We show that homogeneous and isotropic solutions are stable under small nonlinear perturbations without any symmetry assumptions. Our proof is based on results on the nonlinear stability of de Sitter spacetime and Kaluza-Klein reduction techniques.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…It can also be demonstrated that initially expanding solutions for initial data induced by the Einstein field equations with a positive cosmological constant and coupled to various reasonable matter models exist globally in time [183]. In particular, global results are possible for inflationary scalar field cosmological models with an exponential self potential in which the rate of expansion increases polynomially with cosmological time [184,185]. We note that inflationary behaviour also occurs for scalar field models with a power law self potential, but this arises at intermediate times and not to the asymptotic future.…”
Section: Stability Of De Sitter Spacetimementioning
confidence: 99%
“…It can also be demonstrated that initially expanding solutions for initial data induced by the Einstein field equations with a positive cosmological constant and coupled to various reasonable matter models exist globally in time [183]. In particular, global results are possible for inflationary scalar field cosmological models with an exponential self potential in which the rate of expansion increases polynomially with cosmological time [184,185]. We note that inflationary behaviour also occurs for scalar field models with a power law self potential, but this arises at intermediate times and not to the asymptotic future.…”
Section: Stability Of De Sitter Spacetimementioning
confidence: 99%
“…Models with a scalar field with an exponential potential are also inflationary because the rate of (volume) expansion is increasing with time, and global results are possible [240,241]. Inflationary behaviour also arises in the presence of a scalar field with a power law potential, but occurs at intermediate times rather than at late times.…”
Section: Stability Of De Sitter Spacetimementioning
confidence: 99%
“…Models with a scalar field with an exponential potential are also inflationary because the rate of (volume) expansion is increasing with time, and global results are possible [240,241]. Inflationary behavior also arises in the presence of a scalar field with a power law potential, but occurs at intermediate times rather than at late times.…”
Section: Stability Of De Sitter Spacetimementioning
confidence: 99%